Income Diversification as Income Maximizing Strategy - Lechthaler, Wolfgang (Journal of Income Distribution®, 2011)
In a simple model, I demonstrate that the U-shaped relationship between income and income diversification typically found in developing countries can be explained without any risk considerations. It might be the result of pure income maximization in an environment with limited possibilities.